Analisis Kasus Pending Klaim Pelayanan Asuransi BPJS Kesehatan Rumah Sakit PKU Muhammadiyah Temanggung - Muh Amin; Zaenal Arifin; Yuni Indrawati (Universitas Pahlawan Tuanku Tambusai, 2026)
BPJS Kesehatan (the health social security administration) was implemented in 2014 as the national health insurance system (JKN) to provide affordable healthcare services. BPJS Kesehatan service reimbursement processes use the INA-CBGs (Indonesia-Based Groups) system. A common problem faced by hospitals is pending claims, which impacts operational costs, salaries, drug procurement, service quality, and public trust. Recommendations are needed to improve claim quality and create a more effective and efficient claims system. The objective is to analyze the types of pending claims, their causes, and improvements to prevent pending claims for BPJS Kesehatan insurance services. The research method used is a mixed methods study with a sequential explanatory design. Primary data collection consisted of a recapitulation of pending claims cases from January to March 2025 and in-depth interviews. The results of the study showed that pending claims were 1.99% in January, 2.83% in February, and 2.23% in March. Types of pending claims; the highest clinical type was in February 60.9%, the highest coding type was in March 33.6%, and the highest administrative type was in January 28.6%. Causes of pending claims for clinical types; diagnosis lacks supporting evidence, no supporting examinations, supporting results do not support the diagnosis. no treatment is provided, as PPK 1 competency, service episode. Types of coding; placement of primary and secondary diagnoses is inappropriate, supporting data is lacking in the diagnosis, differences in perceptions between BPJS coders and verifiers, coder accuracy. Types of administration; incomplete files, SEP incompatibility, incorrect treatment billing entries. Prevention of pending clinical claims; improving communication between doctors, coders and internal verifiers, monitoring by MPP on clinical data, socialization of FKTP competencies. Types of coding; Coding verification, coding of diseases and procedures according to medical record-based evidence, improving understanding between coders and BPJS verifiers, updating coders with regulatory information and participating in training. Types of administration: data combination application, socialization of completeness of BPJS Health claims administration.